DIVERSIFICATION OF OYSTER MUSHROOM (Pleurotus Ostreatus) MEDIA FROM AGRICULTURAL WASTE MATERIALS - Widiwurjani Widiwurjani (UNEJ e-Proceeding, 2017)
Utilization of agricultural wastes needs to be researched and developed so there is adiversification media of oyster mushroom nursery. Waste must contain lignin and protein.Lamtoro seed and cotton seeds can replace corn. Tofu and soy replace bran. The researchobjective is to get the oyster mushroom nursery media from agricultural and agro-industrialwaste. The treatments tested are main media: corn, lamtoro seed, cotton seed and Factor II:Starter bran, tofu and soy skin. Complete randomized design was repeated 3 times.Parameter observations include water content, pH, organic C, total N and C / N ratio, rate ofgrowth, weight of mycelium and production of fresh oyster mushrooms of various seedscultured in media tested. The results is 3-5% moisture content, pH 6.5-7.2, 42-46.4% organicC value, the value of 0.73-1.35% total N and C / N ratio of 33.87-58.90. Media derived fromthe lamtoro seeds provide the lowest growth. Mycelium weight reaching 23-25 grams, andspeed of weight gain 1.70-2.66 g / day. 800 - 1100gr per bag log mushroom production.Conclusion is oyster mushrooms can be grown on media from agricultural and agroindustrywaste and the ability to produce fresh oyster mushrooms are not significantly different fromcontrols.